Analisis Strategi Promosi Syariah Melalui Pemanfaatan Media Sosial Instagram Dalam Mengembangkan Usaha - RD. Andre Putra Al Abyadi; Sri Rahma; Rabiyatul Alawiyah (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
The development of information technology, particularly social media, has brought significant changes to marketing strategies. In sharia-based businesses, the application of Islamic principles serves as the main foundation to ensure that every transaction is not only materially profitable but also halal, honest, and brings blessings. Social media, especially Instagram, has become an effective medium for entrepreneurs to promote products, build customer trust, and expand market reach. Astech Komputer, a computer service and sales business located in Jambi City, serves as a real example of utilizing social media in implementing sharia-based promotional strategies. This study aims to analyze the sharia marketing strategy applied by Astech Komputer through Instagram and to identify the challenges faced in its implementation. The objective is to determine the effectiveness of social media as a promotional tool that aligns with Islamic principles in developing business growth. This research employs a qualitative method with a field research approach. Data were collected through observation, interviews with the business owner, and documentation of promotional activities on Instagram. The results show that the sharia marketing strategy implemented by Astech Komputer through Instagram is effective in increasing customer trust and supporting business growth. The strategy is carried out through two main aspects, namely advertising and sales promotion, both of which are based on Islamic values such as shiddiq (honesty), amanah (trustworthiness), tabligh (communicativeness), fathanah (wisdom), and istiqamah (consistency). The application of these values is reflected in the transparent, honest, and deception-free presentation of information. Despite facing challenges such as high paid promotion costs and competition among similar businesses, the strategy still has a positive impact on the business growth of Astech Komputer